2023
DOI: 10.7759/cureus.38053
|View full text |Cite
|
Sign up to set email alerts
|

Study of Demographics, Clinical Profile and Risk Factors of Inguinal Hernia: A Public Health Problem in Elderly Males

Abstract: Background: Inguinal hernia repair is the most commonly performed elective surgery in India draining significant healthcare resources. This observational study was conducted at a tertiary-level institute in northern India to look into the demographics, clinical profile and risk factors of inguinal hernia. Method: This study was conducted as an observational study at the tertiary care centre of northern India, including 110 patients who had come to the surgical outpatient department for inguinal hern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…So this is what is most likely to cause symptomssyndrome dyspepsiafelt by the patient.Based on the results of several previous studies and supporting theories, the researchers concluded from the existing data that 37 patients (88.1%) had a primary diagnosis of inguinal hernia and 5 patients (11.9%) had a diagnosis of inguinal hernia15 This research is also in line with research conducted by Merry et al, that older people have a greater risk of experiencing inguinal hernias.…”
supporting
confidence: 69%
“…So this is what is most likely to cause symptomssyndrome dyspepsiafelt by the patient.Based on the results of several previous studies and supporting theories, the researchers concluded from the existing data that 37 patients (88.1%) had a primary diagnosis of inguinal hernia and 5 patients (11.9%) had a diagnosis of inguinal hernia15 This research is also in line with research conducted by Merry et al, that older people have a greater risk of experiencing inguinal hernias.…”
supporting
confidence: 69%
“…Notably, approximately 71% of the patients exhibited an indirect type of hernia, consistent with findings in other comparable studies. In a prior study within the same geographical region, Agarwal noted a 60% presentation of indirect hernias, while Rao et al reported 83.61% [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%